2019
DOI: 10.1097/jsm.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Sports Specialization Is Not Associated With Greater Odds of Previous Injury in Elite Male Youth Soccer Players

Abstract: Objective: To determine the relationship between sport specialization and previous injury in elite male youth soccer players. Design: Retrospective survey. Setting: U.S. Soccer Development Academy. Participants: Male youth soccer players (N = 2123). Assessment of Risk Factors: Sport specialization, weekly training vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 14 publications
0
25
1
Order By: Relevance
“…In a sample of 2123 elite male youth soccer athletes, there was no association between specialization and overuse injury. 8 In a separate study, specialized individual-sport athletes were more likely to report an overuse injury compared with specialized team-sport athletes. 17 Highly specialized youth tennis players are also more likely to report an injury.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a sample of 2123 elite male youth soccer athletes, there was no association between specialization and overuse injury. 8 In a separate study, specialized individual-sport athletes were more likely to report an overuse injury compared with specialized team-sport athletes. 17 Highly specialized youth tennis players are also more likely to report an injury.…”
Section: Discussionmentioning
confidence: 94%
“…Sport-specific examinations of specialization risks in youth sports are lacking, with 2 studies finding an association of specialization and overuse injury in youth tennis athletes 11 and youth soccer athletes 1 and another recent study finding no association in elite youth soccer players. 8 Therefore, the primary purpose of this study was to examine sport-specific associations of sex, sport specialization, and exceeding sport volume recommendations with overuse injuries in adolescent basketball, soccer, and volleyball athletes. We hypothesized that female athletes would be more likely than male athletes to report an overuse injury in the previous year, regardless of sport.…”
mentioning
confidence: 99%
“…59,[66][67][68] There are few data regarding sport specialization and injury risk specifically among soccer players, with a single recent study of elite male adolescent soccer athletes revealing that specialization was associated with a decreased risk of previous injury overall and was not related to previous overuse injury. 69 Inadequate sleep and fatigue have been shown to be risk factors for injury in youth athletes, 60,70 although this has not been specifically studied in soccer. Finally, overtraining is considered an important risk factor for injury in a number of sports, and acute increases in training load have been shown to be an independent risk factor for injury in youth soccer players, perhaps as a result of impairments in sleep and subjective well-being, which serve as early indicators of overtraining.…”
Section: Injury Risk Factorsmentioning
confidence: 99%
“…24 Similarly, a recent study in soccer players demonstrated no link between specialization and injury risk. 25 Therefore, a sport specific study in collegiate athletes may be beneficial to better understand the possible association of high school sport specialization with collegiate injuries and how this may vary between sports.…”
Section: Discussionmentioning
confidence: 99%